(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
The paper elaborates on the way English language is taught in Poland. Firstly, the author wishes specify the division between different types of schools which create Polish education system. Secondly, the article intends to present the methods which are being used to create a lesson on different levels of education and how many hours of English students are exposed to. Finally, the paper is to show the approach to English in Poland.